Analisis Citra Perempuan dalam Iklan “Lux – Isyana Sarasvati” dan “Pantene – Labels Against Women” dalam Perspektif Feminisme Sosialis - Nursetiyawati, Puri Septiana; Julianti, Shinta (JCIC : Jurnal CIC Lembaga Riset dan Konsultan Sosial, 2025)
This article analyses the representation of women in two popular advertisements, "Lux – Isyana Sarasvati" and "Pantene – Labels Against Women", through the lens of socialist feminist theory. The study focuses on the portrayal of women's roles, identities, and societal expectations within these advertisements, as well as the messages conveyed regarding gender construction. The application of socialist feminist theory aims to examine the role of advertising in either reinforcing or challenging traditional stereotypes about women through its connection to social, economic, and power structures. The "Lux – Isyana Sarasvati" advertisement emphasizes the image of a beautiful and graceful woman as a symbol of social status, whereas "Pantene – Labels Against Women" raises awareness of gender-based discrimination by critiquing the social labels attached to women. The analysis reveals that although both advertisements attempt to promote a positive image of women, they remain entangled within capitalist narratives that commodify women's bodies and identities. This article also underscores the need for a more critical and progressive approach to the portrayal of women in advertising media, one that better reflects women’s social roles in an equitable and empowering manner.